Aspects of using the "omission" technique in translating Arabic texts into Kazakh " - Akhmetbekova, А.; Zhiekbayeva, A.; Seitmetova, Zh. (Journal of Oriental Studies, 2021)
In the theory of translation, various transformations are justified in order to achieve the maximum result of the equivalence of the source text during translation. Among translation strategies, the “omission” technique requires the translator to be highly qualified. Moreover, the applied aspects of this technique are determined by the specifics of each language. In this regard, in the article, we focus on two aspects of the "omission" technique when translating an Arabic text into Kazakh: grammatical and lexical. The article considers the grammatical inconsistencies of the Arabic language and Kazakh language, it analyzes the use of the "omission" technique in the process of translation from Arabic into Kazakh. The article, examines the grammatical inconsistencies of the Arabic and Kazakh languages, and analyzes the use of the "omission" technique in the process of translation from Arabic into Kazakh. This analysis reveals that the "omission" technique is not used automatically, even when a certain topic in one language does not occur in the other, but can be used depending on the context and discourse, although the grammatical categories in the languages are the same. The use of the "omission" technique in relation to lexical units directly depends on the competence of the translator and their interest in preserving the norm of the target language. The qualification of a translator is determined by the fact that the essence of the information in the source text is not distorted, and corresponds to the original as much as possible and does not prejudice the language norm of the recipient. Key words: translation, transformation, “omission” technique, inconsistency, language norm, Arabic language, grammatical category.